HUBUNGAN ANTARA TINGKAT PENGETAHUAN TENTANG POSISI MENYUSUI DAN PERLEKATANNYA DENGAN KEJADIAN PUTING LECET - Regina Vidya Trias Novita; Ika Putri Ayu (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Sore nipples are injuries characterized by wounds, cracks, or gaps in the nipples, one of the problems often experienced by breastfeeding mothers and can cause discomfort to premature cessation of breastfeeding (Wirakhmi & Purnawan, 2021). One of the factors that plays a role in the occurrence of this condition is the mother's lack of understanding of the correct breastfeeding position and attachment. The purpose of this study was to analyze the relationship between the level of knowledge about breastfeeding positions and attachments with the incidence of sore nipples. This research method uses an analytical design with a cross-sectional approach. The sample consisted of 50 breastfeeding mothers selected through purposive sampling techniques according to the inclusion criteria. Data were collected using a questionnaire to assess the level of knowledge and direct observation of the incidence of sore nipples. Data analysis was carried out using the chi-square test to see the relationship between variables. The results of the statistical test showed that most respondents had a high level of knowledge regarding the correct breastfeeding position and attachment, indicating a significant relationship between the mother's level of knowledge and the incidence of sore nipples (p < 0.021). These findings suggest that the majority of respondents understand the importance of proper breastfeeding techniques, which contributes to the prevention of sore nipples. Conclusion: There is a significant relationship between the level of mother's knowledge about breastfeeding position and attachment with the incidence of sore nipples. Therefore, more intensive education is needed regarding the correct breastfeeding technique to prevent sore nipples and support the success of exclusive breastfeeding.